Implementasi Kurikulum Merdeka pada Pelaksanaan Pembelajaran di MAN 1 Kota Padang - Fina Olivia; Nita Putri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to evaluate the implementation of the Merdeka Curriculum in the learning process at MAN 1 Kota Padang, specifically focusing on the preliminary, core, and closing stages. The method used is a descriptive qualitative approach with data collection techniques through classroom observations, interviews with mathematics teachers in grades X and XI, and document analysis of teaching modules. Observation results show high effectiveness levels across all learning stages: preliminary activities reached 100% (grade X) and 80% (grade XI), core activities reached 85.71% (grade X) and 93.33% (grade XI), and closing activities reached 81.81% in both classes. The findings indicate that teachers have implemented learning stages in accordance with the characteristics of the Merdeka Curriculum through context-based learning and differentiated approaches. Learning takes place actively and is relevant to students' lives, although there are obstacles such as limited technology resources and difficulties faced by teachers in independently developing modules. Overall, the implementation of learning is considered effective in increasing student participation and strengthening character values. This study shows that the Merdeka Curriculum has great potential in improving the quality of education in madrasah with continuous support through training and adequate facility provision.